Reproductive and Maternal Health Challenges of Pregnant Women in Ethiopia: An Anthropological Appraisal - Pati, R. N. (International Journal of Social Sciences and Management, 2017)
A very Poor attention is given to reproductive health issues of pregnant women in rural regions of African countries. Ethiopia is one of the countries in horn of Africa representing highest maternal mortality rate in the continent. The Government of Ethiopia has reformed health policy and program to promote community involvement in maternal health, promotion of emergency obstetric health care, health seeking behavior for optimal utilization of maternal health services by women during pregnancies. The women living in pastoralist and small land holders’ communities are exposed to high risks of reproductive health hazards. Material delays comprising of delay in making the decision for referral, delay in arriving at hospital and delay in receiving appropriate maternal health services are major contributing factors for growing maternal deaths in Ethiopia. The illiteracy of woman, exposure to frequent pregnancies at adolescent age, poor decision making power of women in patriarchal society, poor employment status of women are main predicators of low utilization of maternal services and high ,maternal death in rural regions of the country. This article is based on synthesis of research projects completed by different authors on multiple dimensions of maternal mortality in Ethiopia. The promotion of referral support service and bridging up the referral gaps would address issues of maternal mortality and growing unsafe abortions among young mothers in rural regions of the country. This paper examines critically different socio – cultural barriers that prevent women living in rural area for accessing appropriate utilization of maternal and health services and infrastructure available. Int. J. Soc. Sc. Manage. Vol. 4, Issue-1: 32-37